Elevating photovoltaic efficiency: Cobalt doping approaches with sustainable transition metal cations in lead halide perovskite solar cells - M.I. Khan; Saddam Hussain; M. Atif; J.E. Leal-Perez; B.A. García-Grajeda; J.M. Mendivil-Escalante (Results in Chemistry)
Power conversion efficiency (PCE) of the perovskite solar cell in its pristine form is excellent, and its performance increases upon modification with a 3 % concentration of Co2+-MAPbI2Br by the sol–gel spin coating method. X-ray diffraction analysis has attested to the successful integration of Co2+ ions into the cubic structure of MAPbI2Br. It is worthy of note that 3 % Co2+ doping films exhibited an enlarged grain size that is considered a factor that would raise device performance. Further assessment of the optical properties by UV–Vis analysis reveals that the incorporation of 3 % Co2+ doping into MAPbI2Br reduced the band gap energy to 1.84 eV. All in all, in terms of important solar cell performance metrics, the introduction of 3 % Co2+ doping to MAPbI2Br has led to significant improvements. In particular, FF increased to 0.75, and this was accompanied by enhancements in Jsc to 7.83 mA cm−2, Voc to 1.02 V, and η to 5.85 %. Remarkably, these improvements in important factors bring attention to the advantageous effect of Co2+ doping. We have attempted to contribute our work to the perovskites that are still under development in the organic–inorganic world for solar cell technology. We propose that our findings hold substantial knowledge that will contribute to the improvement and development of perovskite solar cells.